Cardiac function and heart rate variability during a multi-stage cycling event: a case study - Menard, V.; Barrero, A.; Lachard, T.; Robinault, L.; Li, L.; Schnell, F.; Carré, F.; Le Douairon Lahaye, S. (27th Annual Congress of the European College of Sport Science (ECSS), Sevilla, 30. Aug - 2. Sep 2022, 2022)
INTRODUCTION: Due to high cardiac workload, prolonged intense exercise results in an exercise-induced cardiac fatigue (EICF) (1). This phenomenon is characterized by transient cardiac function alterations associated to an increase in the cardiac damage biomarkers after athletes performed this type of sport events whether isolated or repeated over several days (2). The EICF is generally assessed by conventional echocardiography and/or cardiac biomarkers, but these tools are expensive and require highly qualified bio-medical staff. The cardiovascular control by autonomous nervous system (ANS) can be assessed by heart rate variability (HRV) analysis. Due to strong relationship between ANS, HRV and cardiac function, we can consider the interest of the HRV analysis for determined EICF. The objective of the study was to describe the evolution of cardiac function and HRV parameters during a multi-stage cycling event and to determine their relationship.